Supercapacitor and magnetic properties of NiO and manganese-doped NiO nanoparticles synthesized by chemical precipitation method - Mala, Nazir Ahmad; Dar, Mohd Arif; Rather, Mehraj ud Din; Reshi, Bilal Ahmad; Sivakumar, S.; Batoo, Khalid Mujasam; Ahmad, Zubair (Journal of materials science. Materials in electronics, 2023)
In this research paper, pristine nickel oxide (NiO) and Mn-doped nickel oxide nanoparticles (NPs) were manufactured through the chemical precipitation method. The X-ray diffraction (XRD), Fourier transform infrared (FT-IR), UV–Visible diffuse reflectance spectroscopy, scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDX), transmission electron microscopy/selected area electron diffraction (TEM/SAED), vibrating sample magnetometer, and cyclic voltammetry were used to examine the pristine and Mn-doped NiO NPs. The XRD results confirmed that all the samples exhibit face-centered cubic structures with decreasing crystallite sizes. SEM and TEM studies show NPs have spherical morphology. The deviation in-between the high energy bandgap and optical absorption has been investigated in pristine and Mn-doped samples. The presence of a peak in the FT-IR spectra at 446 cm −1 confirmed the creation of the NiO phase. Hysteresis measurements show the exchange of weak ferromagnetic to superparamagnetism in the samples due to incorporation of Mn ions. It has been confirmed that the highest capacitance was measured at 555 F/g with a 10 mV/s scan rate for pristine NiO samples. In this research, the pristine NiO and Mn-doped NiO NPs can be used in data storage and supercapacitor applications.